YADNYA: SACRIFICING IDENTITY - OFFERING AWARENESS - Putra, I Gede Jaya; Wulansari, Vita (Proceeding International Conference on Information Technology, Multimedia, Architecture, Design, and E-Business, 2024)
This study explores the artistic process inspired by Pura Segara Ulun Danu Batur, an iconic Balinese temple, and its unique ceremonial landscape during the 1945 Danu Kerthi Isaka Great Work Ceremony. The temple, celebrated for its connection to water sustainability and cultural preservation, serves as a site of deep observation and reflection. The research integrates the concepts of "feel processing" and "logic processing"—the former emphasizing intuition and emotional sensitivity, and the latter focusing on analytical and theoretical approaches—to craft artistic expressions that balance personal identity with the contextual richness of the site. In the creation of Painting on the spot, a method of creation is used that brings the understanding of Yajna closer as a visualization process. Yajna is not merely a ritual, but most importantly, yajna is a symbolic action or work that is understood as a concept in the framework of opening the Path of self-sublimation. The word Yajna comes from Sanskrit, namely from the word "yaj" which means to worship or pay homage, also means to offer or act as an intermediary. From yaj comes the word "yaja" (words in worship), "yajata" (worthy of receiving respect), "yajus" (sacred, rite, religion) and "Yajna" (worship, prayer, offering). A plein-air technique, painting on the spot, was employed to capture the immediacy of rituals, landscapes, and symbolic elements within a limited time frame. This method challenges the artist's capacity to preserve personal identity while responding to the ceremonial vibrancy and environmental beauty. By merging spontaneity with the reflective process, the study highlights how artistic identity emerges through the interplay of individual expression, cultural context, and environmental immediacy. This approach redefines the artist's role as a mediator between self-awareness and the dynamic, living traditions embodied in Pura Segara Ulun Danu Batur.